Neeuro: Revolutionising digital therapeutics through open innovation - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2022)
The case begins in January 2016. Alvin Chan, CEO of Neeuro, reflects on the company’s three-year journey to bring their proprietary wearable technology EEG (electroencephalography) headband to market. The headband was meant for use alongside Neeuro’s mobile applications to improve the brain health of users by reading and interpreting their brain signals. Chan and his co-founder Eddie Chau had long-standing connections and working relationships with government agencies and government-linked research institutes. Neeuro was a start-up, but through open innovation, they were able to access resources and technologies outside of their firm, and quickly build up their technical capacity. Chan forged a positive connection with A*STAR, the Singapore government-linked group of research institutes. Neeuro’s co-founders leveraged their understanding of the surrounding ecosystem, and were able to navigate issues coming out of the scientific community and complex licensing and contracts. Neeuro received two technical capacity-building grants, embedding A*STAR researchers into the company to develop technology in-house and publish a White Paper detailing the scientific background of Neeuro’s technology. They reached patent licensing agreements with A*STAR that boosted their product development cycle, and with the aid of A*STAR’s scientists working with them, Neeuro enjoyed a smooth transfer of technology. Neeuro was well-positioned to succeed, but it remained to be seen if, as Tech in Asia put it, “the hardware [would live] up to its promise of providing demonstrable benefits for your brain function” when compared against existing mental health games. Would it succeed?